Design of concrete structures - Nilson, Arthur H., Prof.; Darwin, David (New York : McGraw-Hill, 1997)
Introduction; Materials; Flexural analysis and design of Beams; Shear and diagonal tension in beams; Bond, anchorage, and development length; Serviceability; Analysis and design for torsion; ..
Includes bibliographical references and index.
Keywords: Reinforced concrete construction; Prestressed concrete construction; Reinforced concrete construction